Marketing strategies and their effect on sales growth at taichan and grills Medan Johor - Ihdina Gustina; Dedy Lazuardi (Trigin Publisher, 2025)
This research aims to determine how much influence promotion and location on sales volume at Taichan and Grills. The research methodology used is descriptive quantitative method. The population in this study is unkwown. The technique for determining the number of samples used in this study used is Hair technique and amounted to 100 respondents. The research method used is the technique of collecting data through questionnaires distribution, library research and field research which is carried out systematically based on the research objectives. The analytical method used to solve the problem and prove the hypothesis is descriptive analysis, regression analysis. This analysis includes validity and reliability, classic assumption test, multiple regression analysis, hypothesis testing through t and F test, and test the coefficient of determination (R2). Promotion dan location variables partially had a positive and significant on Sales Volume at Taichan and Grills Karya Wisata Medan Johor. Promotion and Location variables simultaneously had a positive and significant on Sales Volume at Taichan and Grills Karya Wisata Medan Johor.